The Success Factor of Spirituality Towards Customer Satisfaction - Mohamad, Vidyamala; Shaiful Azlan, Abdul; Putit, Lennora; Azim Azuan, Osman; Dwita, Vidyarini (Global Academic Excellence (M) Sdn. Bhd., 2023)
Spirituality is a fundamental aspect of our inner identity that shapes our behaviour in society and cognitive processes. While previous research has primarily examined spirituality from a religious perspective, marketing scholars are now exploring how individuals interact with spiritual products, services, and locations to enhance their spiritual well-being and create meaningful experiences. This has led to a ground-breaking study in the Malaysian mobile service provider industry, where researchers sought to understand how spirituality influences customer satisfaction. The social exchange theory has proven that the exchange of benefits has determined its ability to satisfy individual needs and desires through this study. Using a purposive sampling method, 187 responses were gathered and analysed using the PLS-SEM technique. The results were astounding, revealing that all factors significantly impacted customer satisfaction. Specifically, spirituality mediated the relationship between brand prestige, alternative attractiveness, and customer satisfaction. This discovery has opened new doors for companies to connect with their customers on a deeper level and for researchers to explore the intriguing intersection between brand prestige, alternative attractiveness, and spirituality. On top of that, this study has achieved two critical criteria by looking at spirituality from the perspective of subscribers’ behaviour in society and cognitive processes, eliminating the influence of materialism. The findings anticipate that when mobile service providers offer their best services to their customers, it will bring about significant changes in the industry, leading to a higher quality of life during the endemic. This is especially relevant given the high reliance on digitalisation among customers today. In summary, this study highlights the importance of spirituality in shaping customer behaviour and satisfaction, offering exciting opportunities for companies and researchers alike.